Burning fraction, radial transport, and steady state profiles of multi-species particles in CFETR burning plasmas. (28th May 2020) - Lin, W.S.; Wang, X.G.; Xiao, C.J.; Wang, Z.H.; Kong, D.F.; Lang, Y.
Abstract: The burning fraction of fuel particles is a crucial issue for future fusion reactors. In order to achieve the high tritium burning fraction required by China Fusion Engineering Test Reactor (CFETR) engineering design, fueling depths and quantities should be estimated by particle control analysis for different scenarios. Thus, in this paper, a multi-species fluid model of deuterium-tritium (D-T) fusion plasmas is applied to study radial transport and profile evolution with CFETR parameters under different fueling conditions. In the model, alpha particles are treated with a slowing down model and diffusion coefficients are introduced according to τ E _ 9 8 . Then, in such a self-consistent burning plasma simulation, the results show that the fusion reaction and fueling parameters effect remarkably changes the shape of D/T profiles, while to alphas and helium ash however, the effect of the fueling parameters is much weaker. It is also seen that the burning fraction is increased substantially with the fueling depth, and significantly affected by particle confinement. Furthermore, by substantially raising the D:T ratio to the regime of above unity, the burning fraction can be increased notably, but with a cost of a certain level of fusion power reduction.